Adsorption characteristics of organics in the effluent of ultra-short SRT wastewater treatment by single-walled, multi-walled, and graphitized multi-walled carbon nanotubes. Issue 1 (December 2018) - Zha, Yifei; Wang, Yuanyuan; Liu, Shuzi; Liu, Shuai; Yang, Yaqiong; Jiang, Hangcheng; Zhang, Yuankai; Qi, Lu; Wang, Hongchen
Abstract With a conceptual shift in sewage treatment from 'waste pollution' to 'vehicle of resource and energy recovery' and the further intensification of the energy crisis, the separation and recovery of carbon resources from discharged sewage has gained increasing recent attention in the field of water treatment. The ultra-short Solids Retention Time (SRT) activated sludge process (SRT ≤ 4 d) is highly efficient for separating organic matter and improving the energy recovery rate in wastewater treatment plants, but the effluent quality is relatively poor. If organics in the ultra-short SRT effluent can be reduced further to separate and recover carbon resources, the process may soon replace the traditional activated sludge process. We conducted physical adsorption carbon recovery experiments in an ultra-short SRT (SRT = 2 d) activated sludge system using three carbon nanotubes. Considering that Chemical Oxygen Demand (COD) arises from a mixture of organic compounds, and because humic acid (HA) makes up a large fraction of the effluent and can cause great environmental harm, further experiments were conducted on the adsorption of HA in the effluent COD to three nanotubes. This study proposes a novel method to completely remove organics from the effluent from ultra-short SRT activated sludge processes and reveals nanotube adsorption properties and mechanisms.